The Weed Dynamics and Adaptation in Waterlogged Soybean Cultivation Systems in Swampy Areas: A Literature Review: Dinamika dan Adaptasi Gulma pada Sistem Budidaya Kedelai Jenuh Air di Lahan Rawa: Kajian Literatur - Edi Susilo; Wismalinda Rita; Hesti Pujiwati (Agriculture, 2026)
The potential for soybean development in swampy areas is enormous, but complex weeds still hamper productivity in waterlogged soil conditions. Similarly, in waterlogged soybean cultivation systems, selective pressure from soil hypoxia or anoxia significantly affects the spatial and temporal composition, dominance, and adaptation mechanisms of weeds. This study focuses on the characteristics of swampy land, weed dynamics in swampy land, and an analysis of the dominant adaptive weeds in terms of morphology, physiology, and reproduction in waterlogged conditions and their implications for the weed-soybean relationship. This study shows that, within in single ecosystem, hypoxic terrestrial weeds, phenotypically dominant hypoxic terrestrial weeds, and phenotypically subdominant hypoxic terrestrial weeds are antagonistic. This theory suggests that waterlogged land will reduce the population of hypoxic weeds as an ecosystem response. It also explains theoretically that waterlogged land will reduce hypoxic conditions and weeds. In waterlogged land, it simultaneously reduces hypoxic weeds and their population. Research on waterlogged land also shows that weed management in waterlogged soybean systems requires an integrated approach to water management, cultivation systems, mechanical control, and bioherbicide allelopathy, which is expected to suppress weed dominance and reduce the need for synthetic herbicides. This study also emphasizes that for the development and improvement of weed control in waterlogged soybean cultivation systems, it is necessary to focus more on weed ecology in swampy land.